Analisis Kelayakan Invetasi Pada Usaha Dimsumku.Plw - Moh. Alwi; Iksan Arwin; Muhammad Din; Munawarah (CV. ITTC INDONESIA, 2025)
Based on the investment feasibility analysis of the Dimsumku.PLW business, which combines qualitative and quantitative approaches using primary data from observation, interviews, and documentation, positive financial results were obtained. The calculation of the Payback Period (PP) shows a figure of 2.2 years, Net Present Value (NPV) of IDR 7,477,959, and Internal Rate of Return (IRR) of 45.52%. These findings confirm that the investment can be recovered within 2 years and 2 months, indicating that the business is financially viable and has potential for development in Palu City, Central Sulawesi.